LRP1 - a master regulator of the contractile activity of myofibroblasts - Schnieder, Jennifer; Justus Liebig University Giessen (My University, 2018)
During wound healing, fibroblasts migrate into the wound where they proliferate and eventually differentiate to myofibroblasts. The latter produce extracellular matrix (ECM) components and thus participate in the formation of a new ECM in the lesion. The characteristics of myofibroblasts are the expression of alpha-smooth muscle actin (alpha-SMA) and high contractile activity. The acquisition of the myofibroblast phenotype during wound healing is regulated in a combinatory way by cytokines, e.g. transforming growth factor-beta1 (TGF-beta1), and matrix rigidity. Low density lipoprotein receptor-related protein 1 (LRP1) was also found to control fibroblast to myofibroblast transdifferentiation in kidney and liver. Depending on the organ, this endocytic receptor promotes or suppresses alpha-SMA expression in fibroblasts. In kidney, LRP1 exerts its functions by modulating the TGF-beta1 response. However, it remains elusive whether LRP1 regulates the induction of the myofibroblast phenotype in lung fibroblasts from patients with idiopathic pulmonary fibrosis (IPF).In order to decipher the role of LRP1 in lung fibroblast differentiation, LRP1 was knocked-down in IPF and donor lung fibroblasts. The microarray analysis revealed that LRP1-deficiency significantly perturbs Kegg pathways which describe processes of cytoskeleton modulation in IPF lung fibroblasts but not in donor lung fibroblasts. In contrast, Kegg pathways which describe endocytic processes were significantly perturbed in donor lung fibroblasts but not in IPF lung fibroblasts following LRP1-depletion. The alpha-SMA expression was investigated in the IPF lung fibroblasts which were derived from different IPF patients. Levels of LRP1 mRNA and alpha-SMA mRNA negatively correlated in these cells. In addition, knock-down of LRP1 led to the increase of alpha-SMA protein expression in IPF lung fibroblasts. This effect was not mediated by the canonical TGF-beta1 pathway. In detail, silencing of SMAD3 did not block alpha-SMA expression after LRP1-knock-down. It was furthermore demonstrated that the expression, activation and transcriptional activity of SMAD3 is not affected by silencing of LRP1. Instead, it was shown that the activity of extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK) as well as of the transcription factor c-Jun is elevated after LRP1-depletion in IPF lung fibroblasts. Pharmacological blockage of ERK or JNK in LRP1-expressing and LRP1-deficient IPF lung fibroblasts identified JNK to mediate the suppression of alpha-SMA by LRP1. Combined knock-down of LRP1 and JNK1 confirmed this finding. Moreover, this experiment showed that LRP1 suppresses c-Jun, a downstream target of JNK, in IPF lung fibroblasts. c-Jun can be a component of the transcription factor AP1. Dual-Luciferase Reporter Assay revealed that LRP1 inhibited the transcriptional activity of AP1 under basal conditions and in response to TGF-beta1. Functionally, LRP1 suppressed the contractile activity of IPF lung fibroblasts under basal conditions and after TGF-beta1 treatment. Proliferation and migration were not affected by LRP1-depletion. Collectively, the present study describes the mechanism by which LRP1 inhibits the differentiation of IPF lung fibroblasts to myofibroblasts. In detail, LRP1 limits alpha-SMA expression and the contractile activity of IPF lung fibroblasts by inhibiting the JNK/AP1 signaling pathway.
Keywords: ddc:570